Distribuição e densidade de populacões de Callicebus coimbrai Kobayashi & Langguth 1999, na região do Refúgio de Vida Silvestre Mata do Junco, Sergipe - Rocha, Juliana Cristina ávila Glasherster da (2011)
The titi, Callicebus coimbrai, is a threatened primate endemic to the Brazilian Northeast (Sergipe and Bahia), where it faces critical levels of deforestation and habitat fragmentation. The Mata do Junco State Wildlife Refuge in Capela, Sergipe, represents one of the most important initiatives for the conservation of the species, although little is known about the local population. The present study aimed to estimate the population density and distribution of C. coimbrai with the refuge, and to record remnant populations within the surrounding area. Data were collected between March, 2010, and January, 2011. The main tract of forest at the refuge (522 ha) was surveyed using standard line transect methods, for the estimation of population density, and playbacks, for the mapping of groups. Playbacks were also used to verify the presence of the species in neighboring fragments. A total of 231.4 km were walked during the line transect survey, and the data were analyzed using the Distance program. Using the most reliable estimate of mean group size, population density for titis was estimated to be 28.7 ind./km², while that for a second primate, Callithrix jacchus, was 117.0 ind./km². No significant habitat preference was identified in either species, although titis were observed at significantly higher levels in the forest than Callithrix. In the acoustic survey, 268 of the 342 playbacks received a response (78.4% response rate), and in many cases (n = 164), two to six different titi groups responded simultaneously. Comparisons of these results with equivalent surveys at other sites indicated a much higher population density than that estimated during the line transect survey. These results indicate the need for the development of a standardized procedure for the estimation of population parameters in these primates. For the population survey, SPOT satellite images of the area around the refuge were analyzed, and 16 fragments with potential for the occurrence of titis were identified. Titis responded to playbacks at nine of these sites, although the species was not found in the largest fragments. The combined area of these new sites was 382,5 hectares. While this represents an important advance in the known distribution of the species, the study indicates a clear need for the implementation of effective strategies for the management of local forests and their fauna, in particular, Callicebus coimbrai.